2015
DOI: 10.1002/bip.22677
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Recognition in multiple sclerosis and rett syndrome using a collection of linear and cyclic N‐glucosylated antigenic probes

Abstract: Antibody detection in autoimmune disorders, such as multiple sclerosis (MS) and Rett syndrome (RTT) can be achieved more efficiently using synthetic peptides. The previously developed synthetic antigenic probe CSF114(Glc), a type I' β-turn N-glucosylated peptide structure, is able to recognize antibodies in MS and RTT patients' sera as a sign of immune system derangement. We report herein the design, synthesis, conformational analysis, and immunological evaluation of a collection of glycopeptide analogs of CSF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 28 publications
3
19
0
Order By: Relevance
“…Hence, the negatively charged groups of the two molecules cannot be superimposed efficiently; therefore, the increased affinity observed with peptide 5 cannot be explained in terms of correct mimicry of the relative positions of the two negatively charged groups of the peptide, as compared with the sugar. On the other hand, previously reported conformational studies on parent peptide 1 revealed the presence of a β‐turn around the Ser 2 ‐Glu 3 ‐Thr 4 ‐Thr 5 sequence . In our peptide 5 (and 3 ) a Glu residue replaces Thr 5 , and a stable hydrogen bond between the side chains of residues 2 and 5 (not reported for peptide 1 ) is observed.…”
Section: Resultssupporting
confidence: 40%
See 1 more Smart Citation
“…Hence, the negatively charged groups of the two molecules cannot be superimposed efficiently; therefore, the increased affinity observed with peptide 5 cannot be explained in terms of correct mimicry of the relative positions of the two negatively charged groups of the peptide, as compared with the sugar. On the other hand, previously reported conformational studies on parent peptide 1 revealed the presence of a β‐turn around the Ser 2 ‐Glu 3 ‐Thr 4 ‐Thr 5 sequence . In our peptide 5 (and 3 ) a Glu residue replaces Thr 5 , and a stable hydrogen bond between the side chains of residues 2 and 5 (not reported for peptide 1 ) is observed.…”
Section: Resultssupporting
confidence: 40%
“…Indeed, despite the presence of the N‐terminal PEG extension, when peptide 13 was tested in solution on the immobilized antibody, it showed a K D value of 6.32×10 −7 m , corresponding to a marginal loss of affinity (six‐fold), as compared with the original sequence. We previously observed similar behavior, that is, a modest decrease in affinity due to N‐terminal modification of antigenic peptides, possibly through the introduction of steric hindrance, which, however, did not hamper the use of these peptides in ELISA . Accordingly, using SP‐ELISA, we tested the peptide Ttds‐LSETETdL ( 13 ), which can be efficiently adsorbed on PVC plates.…”
Section: Resultsmentioning
confidence: 77%
“…Experiments were conducted following the previously described SPR protocol [29] properly optimized for the present study. ADA was immobilized on the sensor chip CM5-type surface.…”
Section: Adalimumab Immobilizationmentioning
confidence: 99%
“…Kinetic experiments were conducted following the previously described SPR protocol [29] optimizing the dissociation phase times and regeneration solutions for the present study. Diluted samples were injected in duplicate over immobilized ADA for 120 s at a flow rate of 30 μL/min.…”
Section: Kinetic Experimentsmentioning
confidence: 99%
“…Surface plasmon resonance experiments with peptides in solution were performed using a Biacore T100 instrument from GE Healthcare (Uppsala, Sweden). Experiments were conducted following the previously described SPR protocol, properly optimized for the present study . The V3 loop peptide was covalently immobilized on a CM5‐type sensor chip surface, according to the amine coupling strategy.…”
Section: Methodsmentioning
confidence: 99%